THE INFLUENCE OF PROFITABILITY, LEVERAGE, COMPANY SIZE, AND CAPITAL INTENSITY ON TAX AGGRESSIVENESS (Manufacturing Companies in the Basic and Chemical Industry Sector listed on the Indonesia Stock Exchange 2016 - 2020 Period) - Adelia Yulianti; Imam Hidayat (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
ABSTRACT This study aims to examine the effect of profitability, leverage, firm size, and capital intensity on tax aggressiveness in manufacturing companies in the material and chemical industry sector listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. This study used a sample of 10 companies using purposive sampling technique. The method used in this study is panel data regression, processed with the statistical tool Eviews 12. Test results in this study simultaneously profitability, leverage, firm size, and capital intensity on tax aggressiveness. While partially shows that the variables of profitability, leverage, and capital intensity have no effect on tax aggressiveness. While the size of the company has an effect on tax aggressiveness Abstrak Penelitian ini bertujuan untuk menguji pengaruh profitabilitas, leverage, ukuran perusahaan, dan capital intensity terhadap agresivitas pajak pada perusahaan manufaktur sektor industri bahan dan kimia yang terdaftar di Bursa Efek Indonesia (BEI) priode 2016-2020. Penelitian ini menggunakan sampel sebanyak 10 perusahaan dengan menggunakan teknik purposive sampling. Metode yang digunakan dalam penelitian ini regresi data panel diolah dengan alat statistik Eviews 12. Hasil Pengujian pada penelitian ini secara simultan profitabilitas, leverage, ukuran perusahaan, dan capital intensity terhadap agresivitas pajak. Sedangkan secara parsial menunjukan bahwa untuk variabel profitabilitas, leverage, dan capital intensity tidak berpengaruh terhadap agresivitas pajak. Sedangkan ukuran perusahaan berpengaruh terhadap agresivitas pajak.